2018
DOI: 10.3389/fpsyt.2018.00561
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glutamate and Glutamine Levels in the Cerebrospinal Fluid of Patients With Probable Alzheimer's Disease and Depression

Abstract: Recent evidence suggests that Alzheimer's disease (AD) and depression share common mechanisms of pathogenesis. In particular, deregulation of glutamate-mediated excitatory signaling may play a role in brain dysfunction in both AD and depression. We have investigated levels of glutamate and its precursor glutamine in the cerebrospinal fluid (CSF) of patients with a diagnosis of probable AD or major depression compared to healthy controls and patients with hydrocephalus. Patients with probable AD or major depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 71 publications
3
90
0
3
Order By: Relevance
“…Regarding univariate analysis, glutamine showed negative correlation with MMSE score. Similarly, previous studies showed increased CSF levels of glutamate and glutamine in patients with probable AD 24 . In addition, the glutamate/glutamine ratio showed a reduction in ageing and AD 40 .…”
Section: Discussionsupporting
confidence: 72%
“…Regarding univariate analysis, glutamine showed negative correlation with MMSE score. Similarly, previous studies showed increased CSF levels of glutamate and glutamine in patients with probable AD 24 . In addition, the glutamate/glutamine ratio showed a reduction in ageing and AD 40 .…”
Section: Discussionsupporting
confidence: 72%
“…OPCs establish physical contacts with functionally relevant neuronal domains and form in parallel with neuronal synaptogenesis, including dendrites, somata, nodes of Ranvier and synaptic cleft [110][111][112]. It has been shown that elevated glutamate levels and gene expression of glutamate receptors are found in the plasma, cerebrospinal fluid (CSF) and locus coeruleus of postmortem brains from patients with depression [113]. Although the pathological mechanism is unclear, researchers found that MDD patients treated with the antidepressant venlafaxine demonstrated decreased glutamate levels in CSF, indicating a correlation between the attenuation or dysfunction of the glutamatergic system and antidepressant treatment of MDD [114].…”
Section: Neurotransmitters and Their Receptors In Depressionmentioning
confidence: 99%
“…Their data suggest that CSF glutamate and glutamine levels might serve as a subclinical biomarker of subtle cognitive changes. 37 Further to this, in the brain, most endogenous glutamine is produced by glutamine synthetase (GS). Increased levelsbut compromised activityof GS may explain the increased levels of CSF glutamine in Alzheimer's disease patients.…”
Section: Biological Plausibilitymentioning
confidence: 99%